2024
DOI: 10.5477/cis/reis.181.135
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo medir las posiciones de los partidos en cuestiones de género? nuevos datos para el análisis de la agenda política

Abstract: Esta nota presenta una nueva propuesta para analizar las cuestiones de género en la competición partidista. A pesar de su creciente protagonismo en el debate público, apenas existen indicadores para medir énfasis y posición de los partidos en temas de género. Nuestra propuesta cubre esta laguna basándose en el análisis de contenido cuantitativo de programas electorales y, específicamente, en la extensión del esquema de clasificación del Regional Manifestos Project. Proponemos un nuevo dominio sobre género para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Opposition to gender-based policies were present in VOX's foundational manifesto and party statutes since its inception [23] and explicit anti-feminist discourse was deployed in official parliamentary speeches made by representatives of VOX [24] and posted in their social media accounts on the occasion of the election campaign in Andalusia [25] and 2019 national and other regional elections [18,23]. A content analysis of 73 parties' manifestos concurring to Spanish regional elections in 2019 showed that, in fact, VOX stays alone when it comes to include women-related regressive policy proposals in their political manifestos [26]. Therefore, it seems plausible to consider this factor as a further explanatory element of the reasons for the electoral emergence of VOX.…”
Section: The Vote For the Western European Radical Right: The Spanish...mentioning
confidence: 99%
“…Opposition to gender-based policies were present in VOX's foundational manifesto and party statutes since its inception [23] and explicit anti-feminist discourse was deployed in official parliamentary speeches made by representatives of VOX [24] and posted in their social media accounts on the occasion of the election campaign in Andalusia [25] and 2019 national and other regional elections [18,23]. A content analysis of 73 parties' manifestos concurring to Spanish regional elections in 2019 showed that, in fact, VOX stays alone when it comes to include women-related regressive policy proposals in their political manifestos [26]. Therefore, it seems plausible to consider this factor as a further explanatory element of the reasons for the electoral emergence of VOX.…”
Section: The Vote For the Western European Radical Right: The Spanish...mentioning
confidence: 99%
“…Based on the same methodology as the Manifesto Project, the RMP measures parties' policy preferences and positions in regional (substate) elections (see Alonso, Gómez, and Cabeza 2013). 1 The RMP team has incorporated a new domain of gender-related categories into its coding scheme (Cabeza, Gómez, and Pérez-Tirado 2023). This new coding scheme allows researchers to track both positive and negative mentions of key issues in gender studies, including equal pay, childcare, violence against women, parental leave, gender quotas, and sexual and reproductive rights.…”
Section: Novel Indicators To Measure Party Preferences On Gender Issuesmentioning
confidence: 99%
“…Esta legislatura constituyó, además, un punto crítico en la evolución de la representación política en España, con la incorporación de representantes de partidos de ideología antifeminista (Bernárdez-Rodal, et al, 2022;Cabeza, et al, 2023) en el Congreso. Así, Vox fue la quinta fuerza en abril de 2019 con 24 escaños, pero seis meses después, en noviembre del mismo año, ascendió a la tercera posición en el Congreso, con un millón de votos más y 52 escaños.…”
Section: Introductionunclassified